More than shelter from the storm hunter-gatherer houses and the built environment - Andrews, Brian N.; Macdonald, Danielle A. (University Press of Florida, 2022)
"Discussing case studies from the Pleistocene through Late Holocene periods, this volume offers a robust examination of houses as not only places of shelter but also of memory, history, and social cohesion within mobile cultures"--
Keywords: Wildbeuter; Unterkunft; Hunting and gathering societies / Dwellings / History; Architecture / Environmental aspects / History; Architecture and society / History; Cave dwellers / History; Architecture / Aspect de l'environnement / Histoire; Architecture et société / Histoire; Troglodytes / Histoire; SOCIAL SCIENCE / Archaeology; SOCIAL SCIENCE / Anthropology / Cultural & Social; Architecture and society; Architecture / Environmental aspects; Cave dwellers; History; Aufsatzsammlung